Awareness of Preventive Measures, Knowledge and Attitude of Affected People Visiting COVID-19 Suspected Unit in Nishtar Hospital Multan the Tertiary Care Hospital, Punjab, Pakistan (Medical Forum Monthly, 2022)
Objective: To determine the awareness of preventive measures, knowledge and attitude of the suspected, documented cases of covid-19 or their close family members also, admitted through corona filter counter in corona suspected units in a tertiary care hospital of Multan (Pakistan).Study Design: Descriptive cross sectional studyPlace and Duration of Study: This study was conducted at the suspected wards of Pandemic Corona Virus, Nishtar hospital-Multan from December, 2020 to December, 2021.Materials and Methods: Patients or their attendants admitting through corona filter counter for the suspicion of corona virus infection on the basis of history like cough, shortness of breath, fever from last two weeks, infiltrates on X-ray chest or HRCT sent through corona filter to corona suspected wards were included in the study. Main variables of study were use of preventive measures, knowledge about disease and attitude. SPSS version 23 was used for data analysis.Results: Most of the patients 52.2%, arrived from Multan. 33.3% patients had travel history. Only thirteen patients traveled to abroad and 49.1% had family contact. It was seen that preventive measures, knowledge and attitude were associated with Covid-19 effected patients.Conclusion: Knowledge, attitude and practice of preventive measures was not good in Pakistani population, factors which are influencing good practice were area of living and family contact. Most of infective patients in our study were those who travel recently in high infective areas